PENGARUH KEGIATAN BERMAIN PERAN MENGGUNAKAN ALAT PERMAINAN BOXBAITULLAH TERHADAP PEMAHANAN HAJI ANAK USIA DINI - Nurjaman, Iman; Solehah, Siti Masitoh Amalu; Dian Setianingrum, Silfiana; Haykal Fikri, Muhamad (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
This study aims to determine the effect of using the educational play tool Box Baitullah on the understanding of the pilgrimage to Mecca among preschool-aged children. The research method used is a quasi-experimental quantitative approach with a one-group pretest-posttest design. The subjects in this study consisted of 10 preschool children who were treated using an educational play tool based on the pilgrimage. The data collection instrument consisted of five questions related to indicators of understanding the pilgrimage, which were given before and after the treatment. The results of the normality test showed that the data were normally distributed with a significance value of 0.463 (> 0.05). Subsequently, a paired sample t-test was conducted which indicated that all indicators showed a significant increase (Sig. < 0.05). Before the treatment, only 20% of the children developed as expected, while after the treatment it increased to 90%. This finding indicates that the educational play tool Box Baitullah is effective in enhancing the understanding of the pilgrimage and moral values in early childhood.